Productivity, ownership, and the investment climate : international lessons for priorities in Serbia - Goldberg, Itzhak (Policy research working paper, 2005)
"The authors use data on 27,000 firms from 50 countries, half of which are transition economies, together with the case of Serbia to examine the relationship between productivity, the investment climate, and private ownership of firms. As government capacity to address investment climate constraints is limited, the prioritization of the constraints is critical. Identification of the relative effects of various investment climate constraints and ownership on productivity should serve as a guide for such prioritization. Although ownership has recently received less attention in policy decisions than before, according to the econometric analysis of productivity reported by the authors, private ownership is an equally or more important determinant of productivity than other components of the investment climate. The importance of ownership shows that an unfinished privatization and restructuring agenda might have negative effects on productivity, in parallel to poor investment climate. Another important finding is that countries in which firms complain more about infrastructure tend to have less productive firms. "--World Bank web site